Analisis Kearifan Lokal dan Nilai Pendidikan Karakter pada Novel Pasar Karya Kuntowijoyo - Diana Naibaho; Marlina Agkris Tambunan; Monalisa Frince Sianturi (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2022)
This thesis discusses the analysis of local wisdom and the value of character education in the novel "Pasar" by Kuntowijoyo. The purpose of this study was to describe local wisdom and the value of character education in the novel “Pasar” by Kuntowijoyo. The method used in this study is a descriptive method with a qualitative form, namely local wisdom and the value of character education in the novel "Pasar" by Kuntowijoyo. The data obtained by data collection techniques using reading, listening, recording local wisdom and character education values ??in market novels. Based on data analysis in the novel "Pasar" by Kuntowijoyo, local wisdom was obtained, namely the cultural dimension of wisdom which is divided into 5 (five) dimensions, namely: a) local knowledge related to data and information about the character of local uniqueness, b) local culture related to elements -cultural elements that include value systems, traditions, languages, technology, norms and so on, c) local skills related to community skills and abilities, d) local resources related to availability, access, unique local potential and resources, e) local processes Social is concerned with how a particular society performs its functions. The value of character education obtained is 6 (six) data, namely: a) religious values ??related to attitudes and behavior that are obedient to religious teachings, b) honest values ??are related to behavior that makes him trustworthy in words, actions and so on, c) the value of discipline is related to an orderly behavior and obeys various rules d) the value of hard work is related to behavior that shows a serious effort in overcoming the task and completing the task as well as possible, e) the value of peace-loving related to the attitudes and actions that lead to other people feel happy for his presence, f) the value of reading is related to the habit of providing time to read various readings that provide wisdom g) the value of responsibility is related to a person's attitude and behavior to carry out his duties and obligations to himself, society, the environment and God The Almighty.